2003
DOI: 10.1093/gerona/58.12.m1103
|View full text |Cite
|
Sign up to set email alerts
|

The Mechanisms of Androgen Effects on Body Composition: Mesenchymal Pluripotent Cell as the Target of Androgen Action

Abstract: Testosterone supplementation increases muscle mass primarily by inducing muscle fiber hypertrophy; however, the mechanisms by which testosterone exerts its anabolic effects on the muscle are poorly understood. The prevalent view is that testosterone improves net muscle protein balance by stimulating muscle protein synthesis, decreasing muscle protein degradation, and improving the reutilization of amino acids. However, the muscle protein synthesis hypothesis does not adequately explain testosterone-induced cha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
100
1
6

Year Published

2004
2004
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 176 publications
(114 citation statements)
references
References 47 publications
7
100
1
6
Order By: Relevance
“…Bhasin et al [42] and Singh et al [43,44] hypothesized that androgens promote the commitment of pluripotent stem cells into a muscle lineage and inhibit their differentiation into an adipocyte lineage. The total number of circulating vascular progenitor cells may also be dependent on testosterone levels [45].…”
Section: Testosterone Regulates Cellular Growth and Differentiationmentioning
confidence: 99%
See 1 more Smart Citation
“…Bhasin et al [42] and Singh et al [43,44] hypothesized that androgens promote the commitment of pluripotent stem cells into a muscle lineage and inhibit their differentiation into an adipocyte lineage. The total number of circulating vascular progenitor cells may also be dependent on testosterone levels [45].…”
Section: Testosterone Regulates Cellular Growth and Differentiationmentioning
confidence: 99%
“…The total number of circulating vascular progenitor cells may also be dependent on testosterone levels [45]. Regulation of progenitor cell differentiation is a complex process, dependent on numerous hormones, growth factors, and specific activation of a cascade of gene expression [42,[46][47][48][49][50][51].Critical regulators of adipocyte differentiation include C/EBPα (CCAAT/enhancer binding protein), PPARγ2 (peroxisome proliferator-activated receptor), and LPL (lipoprotein lipase) [47,48,[52][53][54][55][56][57]. Alternatively, transdifferentiation of smooth muscle cells into other phenotypes may occur [58][59][60][61].…”
Section: Testosterone Regulates Cellular Growth and Differentiationmentioning
confidence: 99%
“…Nonetheless, bone is a direct target tissue with respect to androgen action. AR is expressed in the cell types required for skeletal formation and homeostasis, including mesenchymal stromal precursors [4], osteoblasts [1], osteocytes [1,64] and osteoclasts [57]. An additional complication for interpretation of the direct effects of testosterone results from the consequences of its metabolism.…”
Section: Introductionmentioning
confidence: 99%
“…8,9 These observations are not surprising as androgens stimulate mesenchymal pluripotent stem cells towards myogenic lineage instead of adipogenic lineage. 10 A decade ago, a prospective study from the United Kingdom showed that ADT in 22 newly diagnosed men with PCa resulted in an increase in fat mass from 20.269.4 kg at baseline to 21.969.6 kg at 3 months (P50.008), while lean body mass decreased from 63.266.8 kg at baseline to 61.566.0 kg (P50.016).…”
Section: Adt: Body Composition Changesmentioning
confidence: 99%